Suggestopedia Method Effect On Reading Descriptive Text at A Senior High School - Suyadi Suyadi (Universitas Batanghari Jambi, 2021)
Suggestopedia is a teaching method focuses on the teacher-learner relationship while teaching and learning process is going on in the classroom that might be used to encourage the students especially for reading a descriptive text. This study was to explore the senior high school students’ ability on reading descriptive text by using a quantitative method with a quasi-experimental approach. Sample was taken randomly, with 60 students were devided into two groups, 30 students were taken as control class while another 30 students as experimental class. By using a reading text as the instrument of the research, the researcher found that suggestopedia method was proven to be effective with the average pre-test control class was 38,6 and post-test control class was 53,3. The average pre-test in the experimental class was 46 and post-test experimental class was 90,8. The value of t-test higher than the value of t-table was (20,41>2,001) which means that suggestopedia method makes learning process more interesting and more effective for senior high school students.